The Determinants of Cash Holding In the UK after the Financial Crisis - ALGHILANY, ASMA (2017)
Cash holding topic has received a great attention from scholars due to the arguments in which to hold cash or invest it. This argument extends whether the funds should be raised internally or seeks external capital markets. The decision of corporate cash holding is not only depends on academic vision but also on the firm' s role in the market and sensitivity to macro variables. This study aims to determine what variables play major role in making cash holding decision by firms. We specifically study the impact of the financial crisis on UK firms that are listed in FTSE350 during three periods. The data set contains twelve years (2004-2015) data of firm specific variables. This study focuses on the precautionary and financial constrained motives. We find that these motives ply an important role of explaining the cash holdings tendency in three periods. Further we investigate the trade-off and pecking order theories and find that they are used wieldy in the literature due to their influence on the corporate cash holdings. The result shows that FTSE350 dose not tend to accumulate high level of cash even during the financial crisis and prefer to raise funds externally, which implies that they are not financially constrained.